Corrosion fatigue test method suitable for steel rail material

By designing corrosion fatigue test methods suitable for rail materials, simulating the conditions of rails under the action of alternating loads and corrosive media, drawing S-N curves, solving the problem of lack of relevant test methods and judgment basis in the existing technology, and achieving the correct Effective evaluation of corrosion fatigue properties of rail materials.

CN119470095APending Publication Date: 2025-02-18METALS & CHEM RES INST CHINA ACAD OF RAILWAY SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411614650.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art lacks the corrosion fatigue test method for rail materials and its basis for determining, and cannot meet the actual use conditions of rails under the action of alternating loads and corrosive media.

Method used

A corrosion fatigue test method suitable for rail materials was designed. By simulating on-site use conditions, combining sodium bisulfite solution and specific alternating stress conditions, the S-N curve of rail materials in a corrosive environment was drawn.

Benefits of technology

This method can effectively guide the development and inspection of rail materials, provide a basis for determining corrosion fatigue performance, and meet the requirements of corrosion fatigue performance evaluation of rails in actual use environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131840960000051
    Figure BDA0005131840960000051
  • Figure BDA0005131840960000061
    Figure BDA0005131840960000061
  • Figure BDA0005131840960000081
    Figure BDA0005131840960000081
Patent Text Reader

Abstract

The invention relates to a corrosion fatigue test method suitable for a steel rail material. The method comprises the following steps: (1) sample preparation: obtaining a to-be-tested steel rail sample from a to-be-tested steel rail; (2) preparing a corrosion solution, namely a sodium hydrogen sulfite solution, so as to corrode the steel rail sample prepared in the step (1); and (3) test loading: putting the steel rail sample prepared in the step (1) into the corrosion solution prepared in the step (2), and carrying out a corrosion test under loading until the sample fails to obtain an S-N curve, thereby obtaining the corresponding fatigue limit of 2 million times in the corrosion environment. The test method disclosed by the invention has important significance on development of new material steel rails in the railway industry, inspection of existing steel rail materials and service performance evaluation, and can effectively guide use of the steel rails and provide a judgment basis for corrosion fatigue performance of the steel rails.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of railway rails, and in particular relates to a corrosion fatigue test method suitable for rail materials. Background Art

[0002] The service time of rails in some sections of my country's high-speed, conventional and heavy-duty railways has exceeded ten years. The rails are actually in service under the interaction of alternating loads and corrosive media. During long-term use, the rail materials may produce corrosion fatigue phenomena such as crack formation and expansion. In the current standards and technical conditions related to rail materials, the chemical composition and mechanical properties of the materials will directly affect their corrosion fatigue performance, but there are currently no relevant rail material corrosion fatigue test methods and their judgment basis.

[0003] Small specimen corrosion fatigue test is a common test method at present, but it has not been applied to the field of rail materials. In particular, there are no regulations on sampling location, specimen size, corrosion environment and related test loading parameters for the specific service environment of rails, which cannot meet the specific operational requirements of rail corrosion fatigue test.

[0004] Therefore, establishing a standard corrosion fatigue test method for rail materials is of great significance for the development of new rail materials, the inspection of existing rail materials and the evaluation of their service performance. It also plays an important role in expanding scientific research, inspection and technical service businesses in related fields. Summary of the invention

[0005] Aiming at the existing rail materials and related testing methods, the present invention designs the corrosion environment and alternating stress conditions (stress ratio, frequency, waveform, etc.) to carry out corrosion fatigue experiments on the basis of experiments, and draws the SN curve of the rail material under the corrosion environment.

[0006] The corrosion fatigue test method for rail materials of the present invention combines the actual application conditions of rails and the requirements of existing standards, simulates on-site use conditions on the basis of a small sample corrosion fatigue method, and establishes a corrosion fatigue test method for rail materials. This method is of great significance for the development of new material rails in the railway industry, the inspection of existing rail materials, and the evaluation of service performance. It can effectively guide the use of rails and provide a basis for determining the corrosion fatigue performance of rails.

[0007] The present invention is achieved by adopting the following technical solutions.

[0008] In one aspect, the present invention provides a corrosion fatigue test method applicable to rail materials, the method comprising the following steps:

[0009] (1) Sample preparation

[0010] obtaining a rail sample to be tested on the rail to be tested;

[0011] (2) Preparation of corrosion solution

[0012] preparing a sodium bisulfite solution for corroding the rail sample prepared in step (1);

[0013] (3) Test loading

[0014] The rail sample prepared in step (1) is placed in the corrosion solution prepared in step (2), and a corrosion test is performed under loading until the sample fails, so as to obtain an SN curve, thereby obtaining the corresponding fatigue limit of 2 million times under a corrosive environment.

[0015] Preferably, in step (1), the sampling position of the rail sample to be tested is obtained on the rail to be tested according to the sampling position in the specimen fatigue method in the TB / T 2344.1-2020 standard, and the sample is taken from the circular area of ​​the rail head part;

[0016] Preferably, in step (1), a sampling location of a rail sample to be tested is obtained on the rail to be tested such as Figure 2 shown.

[0017] Preferably, in step (1), the size and surface roughness of the rail sample conform to the size and surface roughness in the sample fatigue method in the TB / T 2344.1-2020 standard;

[0018] Preferably, in step (1), the size and surface roughness of the rail sample are as follows: Figure 3 shown.

[0019] Preferably, in step (1), the rail sample is a rod-shaped sample with clamping ends connected by a continuous radius, and the surface of the sample is free of rust and visually visible inclusions and pore defects.

[0020] Preferably, in step (2), the concentration of the sodium bisulfite solution is (1.0±0.05)×10 -2 mol / L.

[0021] Preferably, in step (2), the pH value of the sodium bisulfite solution is between 4.4 and 4.8.

[0022] Preferably, in step (2), the temperature of the sodium bisulfite solution is controlled at 45±2°C.

[0023] Preferably, in step (3), the loading conditions are as follows:

[0024] Loading waveform: sine curve;

[0025] Stress ratio between minimum stress and maximum stress: 0.1;

[0026] Peak stress (i.e. maximum stress): The initial stress is selected as 0.2 to 0.3 times the tensile strength of the rail;

[0027] Cycle frequency: 5Hz.

[0028] Preferably, in step (3), the stress is reduced or increased according to the test result of the previous stress sample. For example, if the fatigue life of the previous sample exceeds 2 million times, the stress of the next sample is increased; if the fatigue life of the previous sample does not reach 2 million times, the stress of the next sample should be reduced, and the stress adjustment amplitude is recommended not to exceed 30MPa each time.

[0029] Preferably, in step (3), the loading is axial loading.

[0030] The test process of the corrosion fatigue test method for rail materials of the present invention is as follows: Figure 1 The specific contents are as follows:

[0031] 1. Sample preparation

[0032] Fatigue tests are axially loaded and the specimen clamping end can be any shape that fits the test machine gripper. A marking method that is indelible and does not affect the test results should be used to identify the specimen, preferably a flat end print.

[0033] Rail steel samples refer to TB / T 2344.1-2020 standard. Figure 2 Samples are taken from the circular area of ​​the rail head of the medium rail; all samples are cut along the rolling direction.

[0034] According to TB / T 2344.1-2020 standard (including the requirements for conventional fatigue specimens of rails), the axial corrosion fatigue test uses a rod-shaped specimen connected by a continuous radius between the clamping ends. At the same time, combined with the requirements of the corrosion fatigue test, the diameter and length of the specimen are adjusted. The specimen size and surface roughness should meet Figure 3 Require.

[0035] The surface of the specimen is not allowed to have rust, visible inclusions, pores and other defects.

[0036] 2. Reagent preparation

[0037] Due to the nature of the interaction between metals and the environment, corrosion fatigue failure experiments must be conducted under closely controlled environmental conditions. Important environmental factors include temperature, solution composition, and pH value.

[0038] The environmental solution is sodium bisulfite solution with a concentration of (1.0±0.05)×10 -2 mol / L, pH value is between 4.4 and 4.8.

[0039] Referring to HG3 1291 standard, the drug used is analytically pure sodium bisulfite.

[0040] Refer to standard GB / T 6682 and use deionized water to prepare the solution.

[0041] The temperature is room temperature and the pressure is normal pressure.

[0042] 3. Test loading

[0043] (1) Waveform

[0044] In some cases, corrosion fatigue strength is strongly influenced by the waveform of the load cycle. Especially when the cycles introduce a delay time, time-dependent corrosion and stress corrosion processes can influence crack initiation and growth. The loading and unloading rates can also influence environmental effects, for example, involving diffusion or repassivation processes, so it is important to apply typical waveforms that will be encountered during actual service.

[0045] The present invention uses a sine curve as a loading waveform.

[0046] (2) Stress ratio

[0047] The stress ratio of the present invention is 0.1.

[0048] (3) Peak stress

[0049] In the initial stage of the experimental research, the peak stress of the corrosion fatigue test is 0.2 to 0.3 times the tensile strength of the rail, and the stress is reduced or increased according to the test results of the previous stress specimen.

[0050] (4) Cycle frequency

[0051] When failure tests are conducted in an "erosive" environment, the frequency of the cycles is much more important than in air, where the frequency of the cycles usually has no effect. The sensitivity to frequency is due to the time-dependent interaction of the metal with the environment. In simple terms, this only reflects the time scale of the entire experiment for effective pit development, while in a broader sense, the cycle period affects the extent of reaction or transmission during a load cycle, and thus the extent of crack development.

[0052] The fatigue strength of a metal or alloy in an "aggressive" environment generally decreases as the cycle frequency decreases. Therefore, it is very important to consider the cycle frequency during the experiment in relation to the actual use.

[0053] In order to ensure that the environment and the sample have sufficient action time and will not seriously reduce the fatigue life of the material, 5 Hz is selected in the sodium bisulfite solution.

[0054] 4. Device

[0055] (1) The fatigue testing machine should meet the use requirements, have the corresponding cycle frequency and waveform signal, and be equipped with appropriate cycle counting and load monitoring systems.

[0056] (2) The fatigue testing machine should be adjusted to ensure that the applied load is axisymmetric.

[0057] (3) The environmental chamber should completely seal the working section of the specimen. If possible, the clamping part of the specimen should be outside the solution environment to prevent battery effects and crevice corrosion. If this is not possible, appropriate avoidance measures should be taken, such as using similar metals, electrical insulation or coatings. An appropriate ratio of solution volume to metal surface area is required (determined by the reaction rate and exposure time), and a circulation system is usually necessary. Non-metallic materials are recommended for making environmental chambers and circulation systems. These materials should be inactive.

[0058] The present invention can use the existing fatigue testing machine to load the environmental box. The schematic diagram of the corrosion fatigue test device is as follows: Figure 4 shown.

[0059] 5. Test process

[0060] The test process of the corrosion fatigue test method for rail materials of the present invention is as follows:

[0061] (1) The specimen is fixed to the specimen fixture of the environmental chamber, and efforts are made to prevent asymmetry due to fixture rotation or movement of the symmetry axis.

[0062] (2) During the experiment, the environment should be tested and controlled as required.

[0063] (3) The test is continued until the specimen fails or a specified number of cycles is reached (e.g. 2 × 10 6 ) can only be terminated when the time comes and cannot be stopped midway.

[0064] (4) The temperature change of the corrosion solution should be controlled within 45±2℃.

[0065] (5) The initial peak stress of the axial corrosion fatigue test in sodium bisulfite solution is taken as 0.2 to 0.3 times the tensile strength of steel. Group tests are carried out, and the stress is reduced or increased according to the number of cycles when the previous stress specimen breaks to obtain the SN curve of corrosion fatigue.

[0066] (6) After the experiment, use acid with corrosion inhibitor to clean the surface rust products. After acid cleaning, rinse with clean water, soak in anhydrous ethanol, blow dry, and store in a desiccator.

[0067] The rail material corrosion fatigue test method of the present invention is guided by field use. Under different alternating stresses, the number of cycles of different stresses is obtained, so that fatigue cracks are generated in the rail material in a corrosive environment and expand to a sufficient size to cause failure. The purpose is to determine the peak stress S at N cycles from the SN curve, thereby obtaining the corrosion fatigue strength at a specified number of cycles, and comprehensively evaluating the corrosion fatigue performance of different rail materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 Flow chart of rail material corrosion fatigue test;

[0069] Figure 2 Schematic diagram of the sample sampling location;

[0070] Figure 3 Shape and size of rod specimens used for axial corrosion fatigue testing;

[0071] Figure 4 Schematic diagram of corrosion fatigue test device;

[0072] Figure 5 A. Rail corrosion fatigue performance;

[0073] Figure 6 B. Corrosion fatigue performance of rails. DETAILED DESCRIPTION

[0074] The present invention is further described below in conjunction with embodiments, which are as follows:

[0075] Example 1

[0076] 1. Test the alloy composition of rail materials

[0077] The alloy composition of the rail material tested in this embodiment is shown in Table 1:

[0078] Table 1 Alloy composition of the tested rail materials (wt.%)

[0079]

[0080]

[0081] 2. Test process

[0082] The test process of this embodiment is as follows Figure 1 The specific contents are as follows:

[0083] 2.1 Sample preparation

[0084] Rail steel samples refer to TB / T 2344.1-2020 standard. Figure 2 Samples are taken from the circular area of ​​the rail head of the medium rail; all samples are cut along the rolling direction.

[0085] According to TB / T 2344.1-2020 standard (including the requirements for conventional fatigue specimens of rails), the axial corrosion fatigue test uses a rod-shaped specimen connected by a continuous radius between the clamping ends. At the same time, combined with the requirements of the corrosion fatigue test, the diameter and length of the specimen are adjusted. The specimen size and surface roughness should meet Figure 3 Requirements: The sample surface is not allowed to have rust and visually visible defects such as inclusions and pores.

[0086] 2.2 Reagent preparation

[0087] According to the iron standard TB / T 2375 (which stipulates the weekly immersion test of weathering steel for railway use), prepare the environmental solution sodium bisulfite solution with a concentration of (1.0±0.05)×10 -2 mol / L, pH value is between 4.4 and 4.8, and temperature is controlled at 45±2℃.

[0088] Referring to HG3 1291 standard, the drug used is analytically pure sodium bisulfite.

[0089] Refer to standard GB / T 6682 and use deionized water to prepare the solution.

[0090] The temperature is room temperature and the pressure is normal pressure.

[0091] 2.3 Test loading

[0092] (1) Waveform

[0093] The loading waveform is a sine curve.

[0094] (2) Stress ratio

[0095] The stress ratio was 0.1.

[0096] (3) Peak stress

[0097] In the initial stage of the test research, the peak stress of the corrosion fatigue test is 0.2 to 0.3 times the tensile strength of the rail, and the stress is reduced or increased according to the test results of the previous stress sample. Specifically: if the fatigue life of the previous sample exceeds 2 million times, the stress of the next sample is increased by 30Mpa; if the fatigue life of the previous sample does not reach 2 million times, the stress of the next sample should be reduced by 30MPa.

[0098] (4) Cycle frequency

[0099] Select 5 Hz in sodium bisulfite solution.

[0100] 2.4 Device

[0101] Schematic diagram of corrosion fatigue test device Figure 4 shown.

[0102] 2.5 Experimental process

[0103] (1) The specimen should be fixed in the specimen fixture of the environmental chamber, and efforts should be made to prevent asymmetry due to rotation of the fixture or movement of the axis of symmetry.

[0104] (2) During the experiment, the environment should be tested and controlled as required.

[0105] (3) The test is carried out until the specimen fails, and the failure effect is completely separated. This test is to exert the effects of corrosion and fatigue at the same time and ensure a reasonable test cycle.

[0106] (4) The initial peak stress of the axial corrosion fatigue test in sodium bisulfite solution is taken as 0.2 to 0.3 times the tensile strength of steel. The test is carried out in groups, and the stress is reduced or increased according to the number of cycles when the previous stress specimen breaks.

[0107] According to the above test process, the fatigue life of rail A in the corrosive environment is measured, as shown in Table 2.

[0108] Table 2 Fatigue life of rail A at different stress levels under corrosive environment

[0109] Sample No. Loading ratio R Maximum stress / MPa Cycle life 1-1 0.1 400 342435 1-4 0.1 380 176185 1-5 0.1 380 229110 1-6 0.1 340 328661 1-7 0.1 280 967350 1-8 0.1 240 1949481 2-9 0.1 220 2378020

[0110] According to the above data, the fatigue curve of the above rails is fitted, and the data processing process is carried out with reference to the standard TB / T 2349-2016, and the linear regression analysis is based on the principle of least squares method. The specific fitting process is:

[0111] The cycle life N is the horizontal axis, and the maximum stress value σ is the horizontal axis. max As the ordinate, a power exponential fitting is performed on it in the logarithmic coordinate to obtain the stress-life fitting equation (SN curve equation of corrosion fatigue):

[0112] Corrosive environment: max =5906.5*N -0.222

[0113] Then convert the power exponential equation into a logarithmic equation:

[0114] Corrosive environment: lgσ max =3.7714-0.222lgN, correlation coefficient r=-0.9637.

[0115] The above SN curve is as follows Figure 5 shown.

[0116] According to the above fitting SN curve equation, the fatigue limit corresponding to 2 million times in a corrosive environment is 235.8MPa.

[0117] (5) After the experiment, use acid with corrosion inhibitor to clean the surface rust products. After acid cleaning, rinse with clean water, soak in anhydrous ethanol, blow dry, and store in a desiccator.

[0118] Example 2

[0119] 1. Test the alloy composition of rail materials

[0120] The alloy composition of the rail material tested in this embodiment is shown in Table 3:

[0121] Table 3 Alloy composition of tested rail materials (wt.%)

[0122]

[0123] 2. Test process

[0124] The test process of this embodiment is as follows Figure 1 The specific contents are as follows:

[0125] 2.1 Sample preparation

[0126] Rail steel samples refer to TB / T 2344.1-2020 standard. Figure 2 Samples are taken from the circular area of ​​the rail head of the medium rail; all samples are cut along the rolling direction.

[0127] According to TB / T 2344.1-2020 standard (including the requirements for conventional fatigue specimens of rails), the axial corrosion fatigue test uses a rod-shaped specimen connected by a continuous radius between the clamping ends. At the same time, combined with the requirements of the corrosion fatigue test, the diameter and length of the specimen are adjusted. The specimen size and surface roughness should meet Figure 3 Requirements: The sample surface is not allowed to have rust and visually visible defects such as inclusions and pores.

[0128] 2.2 Reagent preparation

[0129] According to the iron standard TB / T 2375 (which stipulates the weekly immersion test of weathering steel for railway use), prepare the environmental solution sodium bisulfite solution with a concentration of (1.0±0.05)×10 -2 mol / L, pH value is between 4.4 and 4.8, and temperature is controlled at 45±2℃.

[0130] Referring to HG3 1291 standard, the drug used is analytically pure sodium bisulfite.

[0131] Refer to standard GB / T 6682 and use deionized water to prepare the solution.

[0132] The temperature is room temperature and the pressure is normal pressure.

[0133] 2.3 Test loading

[0134] (1) Waveform

[0135] The loading waveform is a sine curve.

[0136] (2) Stress ratio

[0137] The stress ratio was 0.1.

[0138] (3) Peak stress

[0139] In the initial stage of the test research, the peak stress of the corrosion fatigue test is 0.2 to 0.3 times the tensile strength of the rail, and the stress is reduced or increased according to the test results of the previous stress sample. If the fatigue life of the previous sample exceeds 2 million times, the stress of the next sample is increased by 30MPa; if the fatigue life of the previous sample does not reach 2 million times, the stress of the next sample should be reduced by 30MPa.

[0140] (4) Cycle frequency

[0141] Select 5 Hz in sodium bisulfite solution.

[0142] 2.4 Device

[0143] Schematic diagram of corrosion fatigue test device Figure 4 shown.

[0144] 2.5 Experimental process

[0145] (1) The specimen should be fixed in the specimen fixture of the environmental chamber, and efforts should be made to prevent asymmetry due to rotation of the fixture or movement of the axis of symmetry.

[0146] (2) During the experiment, the environment should be tested and controlled as required.

[0147] (3) The test is carried out until the specimen fails, and the failure effect is completely separated. This test is to exert the effects of corrosion and fatigue at the same time and ensure a reasonable test cycle.

[0148] (4) The initial peak stress of the axial corrosion fatigue test in sodium bisulfite solution is taken as 0.2 to 0.3 times the tensile strength of steel. The test is carried out in groups, and the stress is reduced or increased according to the number of cycles when the previous stress specimen breaks.

[0149] According to the above test process, the fatigue life of rail B in the corrosive environment is measured, as shown in Table 4.

[0150] Table 4 Fatigue life of B rail at different stress levels under corrosive environment

[0151]

[0152]

[0153] According to the above data, the fatigue curve of the above rails is fitted, and the data processing process is carried out with reference to the standard TB / T 2349-2016, and the linear regression analysis is based on the principle of least squares method. The specific fitting process is:

[0154] The cycle life N is the horizontal axis, and the maximum stress value σ is the horizontal axis. max As the ordinate, a power exponential fitting is performed on it in the logarithmic coordinate to obtain the stress-life fitting equation:

[0155] Corrosive environment: max =22958*N -0.309

[0156] Then convert the power exponential equation into a logarithmic equation:

[0157] Corrosive environment: lgσ max =4.3610-0.309lgN, correlation coefficient r=-0.9951.

[0158] The above SN curve is as follows Figure 6 shown.

[0159] According to the above fitting SN curve equation, the fatigue limit corresponding to 2 million times in a corrosive environment is 259.4MPa.

[0160] (5) After the experiment, use acid with corrosion inhibitor to clean the surface rust products. After acid cleaning, rinse with clean water, soak in anhydrous ethanol, blow dry, and store in a desiccator.

Claims

1. A corrosion fatigue test method for rail materials, the method comprising the following steps: (1) Sample preparation obtaining a rail sample to be tested on the rail to be tested; (2) Preparation of corrosion solution preparing a sodium bisulfite solution for corroding the rail sample prepared in step (1); (3) Test loading The rail sample prepared in step (1) is placed in the corrosion solution prepared in step (2), and a corrosion test is performed under loading until the sample fails, so as to obtain an SN curve, thereby obtaining the corresponding fatigue limit of 2 million times under a corrosive environment.

2. The test method according to claim 1, characterized in that In step (1), the sampling position of the rail sample to be tested is obtained on the rail to be tested, and the sampling position is obtained from the circular area of ​​the rail head part according to the sampling position in the specimen fatigue method in the TB / T 2344.1-2020 standard; Preferably, in step (1), the sampling location for obtaining the rail sample to be tested on the rail to be tested is as shown in FIG. 2 .

3. The test method according to claim 1 or 2, characterized in that: In step (1), the size and surface roughness of the rail sample conform to the size and surface roughness of the sample fatigue method in the TB / T 2344.1-2020 standard; Preferably, in step (1), the size and surface roughness of the rail sample are as shown in FIG3 .

4. The test method according to any one of claims 1 to 3, characterized in that: In step (1), the rail sample is a rod-shaped sample with a continuous radius between the clamping ends, and the surface of the sample is free of rust and visually visible inclusions and pore defects.

5. The test method according to any one of claims 1 to 4, characterized in that: In step (2), the concentration of the sodium bisulfite solution is (1.0±0.05)×10 -2 mol / L.

6. The test method according to any one of claims 1 to 5, characterized in that: In step (2), the pH value of the sodium bisulfite solution is between 4.4 and 4.

8.

7. The test method according to any one of claims 1 to 6, characterized in that: In step (2), the temperature of the sodium bisulfite solution is controlled at 45±2°C.

8. The test method according to any one of claims 1 to 7, characterized in that: In step (3), the loading conditions are as follows: Loading waveform: sine curve; Stress ratio between minimum stress and maximum stress: 0.1; Peak stress (i.e. maximum stress): The initial stress is selected as 0.2 to 0.3 times the tensile strength of the rail; Cycle frequency: 5Hz.

9. The test method according to any one of claims 1 to 3, characterized in that: In step (3), if the fatigue life of the previous sample exceeds 2 million times, the stress of the next sample is increased; if the fatigue life of the previous sample does not reach 2 million times, the stress of the next sample should be reduced, and the stress adjustment amplitude each time shall not exceed 30MPa.

10. The test method according to any one of claims 1 to 9, characterized in that: In step (3), the loading is axial loading.